Advection of Mesozooplankton Into the Northern Svalbard Shelf Region - Wassmann, Paul; Slagstad, Dag; Ellingsen, Ingrid (Frontiers in Marine Science, 2019)
The northern Svalbard shelf region is part of the Atlantic advective contiguous domain along which nutrients, phyto- and mesozooplankton are advected with Atlantic Water from the Norwegian Sea along the Norwegian shelf bream and into the Arctic Ocean. By applying the SINMOD model we investigated how much mesozooplankton is advected into the northern Svalbard shelf region. We also compare this supply with the local mesozooplankton production. To achieve this, we selected a box north of Svalbard and calculated the in- and outflux of Atlantic Calanus finmarchicus and Arctic C. glacialis. The average biomass inside the box ranged between 0.5 to 3.0 g C m-2 in March and August, respectively. Annually 18.8 g C m-2 of advected (and locally produced) mesozooplankton would be available for predators inside the box before it is advected out again. The advection of mesozooplankton is about 12 times bigger than the average biomass within the box, implying that grazing upon mesozooplankton in the Atlantic advective contiguous domain is greatly advantageous for pelagic predators. It could represent an important food source for fish and whales in the pelagic. It is suggested that the mesozooplankton encountered on the shelf north of Svalbard derives from populations along the North Norwegian shelf break, in some years as far south than the Lofoten/Vesterålen region. This illustrates the extent and significance of the Atlantic advective contiguous domain for the ecosystems of the European shelf of the Arctic Ocean that depend on feed supply and are thus presumably net-heterotrophic.